LIPID INFILTRATION OF HEPATOCYTES IN THE MORPHOGENESIS OF CHRONIC HEPATITIS C - D. L. Nepomnyashchikh; O. A. Postnikova; E. E. Abramova; O. I. Dorovskaya (Сибирский научный медицинский журнал, 2019)
The aim of the study was to investigate structurally functional features of lipidic infiltration of hepatocytes in a morphogenesis of chronic hepatitis C. Material and methods. A clinical and morphological study of 199 patients with HCV infection markers (139 men and 60 women aged from 20 till 65 years) was conducted. In all cases, a comprehensive study including analysis of blood biochemical parameters, serological markers of HCV replication in blood and liver, viremia level, number of the infected hepatocytes and HCV genotypes was performed. Diagnostic complex included clinical, biochemical, immunoserological methods. Results and discussion. The results of the analysis of structural and functional features of lipid-containing hepatocytes and indicators of replication of virus particles of chronic hepatitis C are provided. For its reproduction HCV enters into complex relationships with the metabolic apparatus of the cell, in which lipid metabolism and related structures – lipid droplets play an important role. The only structural marker that correlates with indicators of virus replication is subcytolemmal small-vesicular lipid infiltration, which can reflect a virus-induced increase in lipid metabolism in the host cell for the effective production of infectious active viral particles.